Płaszczyzny administracji elektronicznej - Błażewski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The provisions of e-government are expressed in various legal acts, therefore there is a variety of ways of regulating the management and control of information. The division into dimensions, which are including collection, storage, transmission and control, allow to create a model of e-governmentThe provisions of e-government are expressed in various legal acts, therefore there is a variety of ways of regulating the management and control of information. The division into dimensions, which are including collection, storage, transmission and control, allow to create a model of e-government
Keywords: e-government; electronic means of communication; ICT systems; management of information